Innovative Methods of Teaching Technical Terminology in NonLinguistic Universities - Badalova Luiza Kholmamatovna (Genius Journals, 2023)
The introduction of innovations in all branches of science and technology, the requirements for automating the transmission and processing of information in various areas of human activity lead to the emergence of new terminological units and, as a result, an increase in the importance of terminology as a means of acquiring and organizing scientific knowledge. The article discusses innovative methods of teaching technical terminology in non-linguistic universities and some features of their use in teaching a foreign language in technical universities.
Keywords: communication; professional; technical specialties